The Relationship Between Perceived Teacher Self-Disclosure And Teacher Credibility Among Public Relations Undergraduates In Universiti Tunku Abdul Rahman - Chew, Choi Kuan; Kow, Yuet Teng; Them, Yu Hong; Yap, Xin Fong; Yeoh, Hui Wen (2017)
This study aimed to determine the relationship between perceived teacher self-disclosure and teacher credibility among Public Relations undergraduates in Universiti Tunku Abdul Rahman (UTAR). To measure the relationship of the variables, Demographic factors, Teacher Self-Disclosure Scale and Ethos/Credibility Scale were used as the tools. Stratified random sampling method was used in this quantitative study. 100 questionnaires were distributed to the first year, second year and third year Public Relations students at UTAR. There are 48 male and 52 female students completed the questionnaires in this research study. Besides, SPSS version 22 was used to analysis the data. Other than that, descriptive analysis, Pearson’s correlation, independent samples t-test, one-way ANOVA and multi-comparisons ANOVA used to proceed data analysis. The findings indicated that there are slight positive correlations between perceived teacher self-disclosure and teacher credibility. However, there is no significant difference in terms of gender and in influencing perceived teacher selfdisclosure and teacher credibility. Researcher also found out that there is no significance difference between year of study, perceived teacher self-disclosure and teacher credibility.